Effect of Soaking in Natural Pesticides from Garlic Bulbs and Liquid Soap on The Mortality of Onion Caterpillars - Nurul Hidayah; Yahdi Yahdi; Multazam Multazam (Indonesian Publication Center, 2024)
Productivity of onion in Bima, West Nusa Tenggara (NTB), caused by rain and attacks from pests, has decreased significantly. One of the pests that often attack onion plants is armyworm (Spodoptera exigua Hubner) which causes 100% damage. To prevent damage, farmers use chemical pesticides to stop armyworm (Spodoptera exigua Hubner) attacks. The use of chemical pesticides has many negative impacts both in terms of the environment and health. To resolve this problem, utilize natural pesticides. Natural pesticides don’t have residual effects and are safe for health. The purpose of this study was to know the effect of natural pesticides garlic and liquid soap against the mortality of armyworms. The methods used are experimental research and a quantitative approach. The result of this study obtained the highest armyworm mortality at 9 days of immersion of 100% and the longer the immersion was carried out the higher the mortality rate of armyworm. Based on the analysis of One Way ANOVA, there was an effect of soaking time of natural pesticides against the mortality of armyworms with a significant value of 0.046.